Penerapan Pembelajaran Permainan Soccer Like Games Untuk Meningkatkan Perilaku Sosial Siswa Kelas VI SD Negeri 4 Manurunge Kabupaten Bone - saleha saleha (Universitas Negeri Makassar, 2019)
This research is a classroom action research to find out to what extent the application of soccer like games learning can develop students' social behavior, with the background of classroom action research at SD 4 Manurunge, Bone. This research consists of four stages, namely: planning, implementing actions, observing and reflecting. The process of collecting data is done through observation of each treatment in the learning process of soccer likes games. Based on the data above shows the aspects of pro-social behavior of students during the learning cycle 2 games like soccer like games have experienced a fairly good and positive improvement/development, this can be seen from the average social behavior of students in the pre-action activities by 62%, 1 cycle action 2 by 68% and in action 2 the 2-cycle cycle is 76%. The enthusiasm of the students in cycle 2 is already quite good, students have been very enthusiastic in the implementation of learning when a game is ended by the teacher, students feel dissatisfied and do not want to end the game, this is evidence that the game of interest and enthusiasm is very high. Based on the results of data processing and data analysis, conclusions in this study are as follows: The application of learning soccer like games with action research background has succeeded in developing the social behavior of Class VI students at SD 4 Manurunge, Bone